2018
DOI: 10.1097/sap.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Infiltrating Lipomatosis of the Face

Abstract: RationaleCongenital infiltrating lipomatosis of the face (CILF) is a rare disorder characterized by collections of nonencapsulated mature lipocytes that infiltrate surrounding tissues. In this article, we would report a new case of CILF, which may be one of the first few cases reported in China.Patient ConcernsAn 8-year-old boy presented with a hyperplasia of subcutaneous tissue of his left face, which had been gradually progressing since birth, resulting in a marked facial asymmetry. Then he underwent an oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“… 30 33 These changes in bone appear to be associated with periosteal irritation associated with the overlying mass, regional malformation of mesenchyme affecting bone and soft tissues or increased vascularity. 30 , 33 , 34 Li et al 35 in their review of 59 reported cases of CILF noted that the bony asymmetry appears to increase with age, with the adipose tissue infiltrating into surrounding tissues and causing pterygoid gland and muscles (such as pterygoid plate and massetter and temporalis muscles) involvement, as reported in our cases.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“… 30 33 These changes in bone appear to be associated with periosteal irritation associated with the overlying mass, regional malformation of mesenchyme affecting bone and soft tissues or increased vascularity. 30 , 33 , 34 Li et al 35 in their review of 59 reported cases of CILF noted that the bony asymmetry appears to increase with age, with the adipose tissue infiltrating into surrounding tissues and causing pterygoid gland and muscles (such as pterygoid plate and massetter and temporalis muscles) involvement, as reported in our cases.…”
Section: Discussionsupporting
confidence: 73%
“… 1 , 4 – 7 The manifestation is always unilateral, and reported cases that described the site of the facial mass have shown that ~64% occur on the left. 10 In CILF patients who present for treatment at the adult stage, the condition progresses with gradual hyperplasia, while there is extensive hyperplasia in childhood patients (≤1 year of age). 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathological examination of this case could see abnormal bro-fatty tissue hyperplasia, the adipocytes were invasive, and part of muscles presented fat degeneration, which is also similar to congenital in ltrating lipomatosis (CIL) , a rare congenital disease initiating from infant [16] . Slavin et al…”
Section: Case Presentationmentioning
confidence: 58%